Pengaruh Brand Image Terhadap Keputusan Penggunaan Kartu Halo Di Tenggarong - Ahmatang, Ahmatang (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2020)
Along with the competition in electronics industries celuler card, has developed so rapidly. Companies use a variety of strategies to win and retain customers, one of which by creating a strong brand image to be the top of mind in the hearts of the customers. This research is to examine the effect of the brand image for the customer in choosing the HALO Card at the Tenggarong . The data of the research was obtained by observing, interviewing, and also spreading out the questionnaire to the respondent. By utilizing the test of multiplied linear regression, the research designates that the image of producer, image of consumer and the image of product variables have significan effect to choose HALO Tenggarong. Based on the result of the linear regression test, it is known that the most significant variables effect the costumer to choose the HALO Card is the image of consumer variable. It is due to the highest beta and also the lowest probability value among other variables. From the test Partial and simultan, the research proves that all of brand image variables (image of producer, image of consumer, and image of product) have the positif and significant effect the costumer decision to choose HALO card.Â Keywords: image of producer, image of consumer, image of product, customer decision